Use of cardiovascular magnetic resonance for risk stratification in chronic heart failure: prognostic value of late gadolinium enhancement in patients with non-ischaemic dilated cardiomyopathy - Lehrke, Stephanie; Loßnitzer, Dirk; Schöb, Michael; Steen, Henning; Merten, Constanze; Kemmling, Helmut; Pribe-Wolferts, Regina; Ehlermann, Philipp; Zugck, Christian; Korosoglou, Grigorios; Giannitsis, Evangelos; Katus, Hugo (Heart, 2011)
Objective Owing to its variable clinical course, risk stratification is of paramount importance in non-ischaemic dilated cardiomyopathy (DCM). The goal of this study was to investigate the long-term prognostic significance of late gadolinium enhancement (LGE) as detected by contrast-enhanced cardiovascular magnetic resonance (CE-CMR) in patients with DCM. Design Observational cohort study. Setting University hospital. Patients 184 consecutive patients with DCM. Measurements CE-CMR was performed on a 1.5 T clinical scanner. Presence, extent and patterns of LGE were determined by two independent observers. Outcome measures Patients were followed for the composite end point of cardiac death, hospitalisation for decompensated heart failure, or appropriate implantable cardioverter defibrillator discharge for a mean±SEM of 685±30 days. Results LGE was detected in 72/184 patients (39%) and was associated with a lower left ventricular (LV) ejection fraction (31% (20.9-42.2%) vs 44% (33.1-50.9%), p<0.001), higher LV end-diastolic volume index (133 (116-161) ml/m2 vs 109 (92.7-137.6) ml/m2, p<0.001) and higher LV mass (80 (67.1-94.8) g/m2 vs 65.8 (55.2-82.9) g/m2, p<0.001). Patients in whom LGE was present were more likely to experience the composite end point (15/72 vs 6/112, p=0.002). Receiver operating characteristic curve analysis revealed a LGE of >4.4% of LV mass as optimal discriminator for the composite end point. When entered into multivariate Cox regression analysis, LGE retained its independent predictive value, yielding an associated HR of 3.4 (95% CI 1.26 to 9). Conclusion The presence of LGE in this large DCM patient cohort is associated with pronounced LV remodelling, functional impairment and an adverse outcome. Further research is necessary to determine whether these findings will aid the clinical management of DCM patients.
Published online first 20 November 2010
Gesehen am 10.08.2022